2022
DOI: 10.1039/d1nr07628k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the activity and selectivity of polymerised ionic liquid-stabilised ruthenium nanoparticles through anion exchange reactions

Abstract: The development of highly active and selective heterogeneous-based catalysts with tailorable properties is not only a fundamental challenge, but is also crucial in the context of energy savings and sustainable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 79 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, the activity and selectivity could simply be manipulated through counter-anion exchange reactions. 113 Kheirabad et al reported the fabrication of functionalized gradient porous PIL membrane-incorporated metal nanoparticles (Fig. 22c).…”
Section: Applicationmentioning
confidence: 99%
“…Interestingly, the activity and selectivity could simply be manipulated through counter-anion exchange reactions. 113 Kheirabad et al reported the fabrication of functionalized gradient porous PIL membrane-incorporated metal nanoparticles (Fig. 22c).…”
Section: Applicationmentioning
confidence: 99%
“…Ionic liquids reactions create a conducive ionic environment for the synthesis of novel structured materials, imparting them with unique and beneficial properties [35]. Recent studies indicate that employing ionic liquids instead of conventional organic or aqueous solvents enables the production of nanoparticles without requiring external capping agents [36].…”
Section: Introductionmentioning
confidence: 99%
“…Vignolle and coworkers synthesized RuNPs stabilized with polymerized ILs (PILs) based on N-vinyl imidazolium and hydrogenated S (40 • C, 15 bar H 2 ) as a model reaction to study the correlation between chemo-selectivity and the nature of counter anion. They showed that I − /NTf 2 − anion exchange enabled the chemo-selective hydrogenation of S to switch from EB to ethylcyclohexane (ECH) [28]. ] and demonstrated that RuNPs stabilized by the former FIL had high activity and selectivity in the hydrogenation of functionalized olefins, aromatic nitro compounds and aromatic aldehydes [29].…”
Section: Introductionmentioning
confidence: 99%